EVOLUTION OF RESEARCH AND COMMUNITY SERVICE INFORMATION SYSTEM (SIMPAS LPPM) INSTITUT TEKNOLOGI KALIMANTANKALIMANTAN INSTITUTE OF TECHNOLOGY - Azhar, Nur Fajri; Nugroho , Bowo; Alfani Putera, M. Ihsan; Kairupan, Muhammad Nasa'i; Ramadhana, Rizky Irswanda (SPECTA Journal of Technology, 2025)
The Research and Community Service Information System (SIMPAS) at the Institute for Research and Community Service (LPPM) of the Kalimantan Institute of Technology (ITK) has evolved since it was introduced in 2018 to improve efficiency and transparency in managing research and community service activities. This research focuses on the development of SIMPAS through technical updates and the addition of features to meet increasingly complex user needs. This evolution includes updating the system environment using the latest version of Laravel, database refactoring to simplify data processing, and adding features such as account registration using Google email and more flexible user role management. This research uses the Scrum methodology in system development, which allows for continuous improvement and focuses on collaboration between teams. The results of this research are expected to optimize the main business functions of LPPM ITK in the process of submitting proposals, selection, to reporting research and community service results, which in turn supports the achievement of the Tri Dharma of Higher Education and regional development. This research also discusses the integration of the system with other related platforms, as well as the potential use of modern technology to support operational security and efficiency.